Analysis of return on investment of sweetpotato seed system interventions in Uganda - Feukeng, F.; Rajendran, S.; Otieno, D.J.; Okello, J.J. (2024)
It is becoming increasingly important for researchers to document the economic and social benefits of new agricultural technologies and efforts made in the research and development of such technologies. This is necessitated by scarcity of financial resources and the increasing pressure from different stakeholders for research and development to generate welfare improvement changes at the smallholder farmer level in sub-Saharan Africa. The current study analyzed the economic impact of the seed system interventions implemented in Uganda by the International Potato Center through two projects: Development and Delivery of Biofortified Crops at scale (DDBIO) and Genetic Advances and Innovative Seed Systems for Sweetpotato (SWEETGAINS). The projects received US$1.463 million and US$ 15 million from the United Kingdom’s Department for International Development, the Foreign Commonwealth and Development Office, and the Bill and Melinda Gates Foundation. The economic surplus and cost-benefit analysis approaches were utilized to estimate aggregate economic benefits and return on investment. Results revealed that during the 23-year lifespan, for every dollar invested, US$ 88.07 was generated for a 6% discount rate, while at a 12% discount rate, every dollar invested generated US$ 82.88 in return. Similarly, the net present value at 6% was US$ 1,626.38 million, while at 12%, it was US$ 1,729.78 million. The overall internal rate of return (IRR) was found to be 50%. Thus, the investments generated positive returns and should be upscaled.